2021
DOI: 10.3390/ijms22179132
|View full text |Cite
|
Sign up to set email alerts
|

Loose Morphology and High Dynamism of OSER Structures Induced by the Membrane Domain of HMG-CoA Reductase

Abstract: The membrane domain of eukaryotic HMG-CoA reductase (HMGR) has the conserved capacity to induce endoplasmic reticulum (ER) proliferation and membrane association into Organized Smooth Endoplasmic Reticulum (OSER) structures. These formations develop in response to overexpression of particular proteins, but also occur naturally in cells of the three eukaryotic kingdoms. Here, we characterize OSER structures induced by the membrane domain of Arabidopsis HMGR (1S domain). Immunochemical confocal and electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…OSER can be induced by two types of proteins: ER-resident membrane proteins and proteins disrupting ER-to-Golgi export (Sandor et al ., 2021). For the former group, there is some controversy in the literature to the necessity of a cytosol-facing oligomerising domain, with some studies showing it to be essential (Yamamoto, Masaki and Tashiro, 1996; Snapp et al ., 2003; Barbante et al ., 2008), while others refuting this claim (Marti et al ., 2010; Jancowski et al ., 2014; Ferrero et al ., 2015; Grados-Torrez et al ., 2021). Recently these opposing views were attempted to be reconciled into a single unified theory of OSER formation, which hypothesised multiple parallel pathways to induce OSER (Sandor et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…OSER can be induced by two types of proteins: ER-resident membrane proteins and proteins disrupting ER-to-Golgi export (Sandor et al ., 2021). For the former group, there is some controversy in the literature to the necessity of a cytosol-facing oligomerising domain, with some studies showing it to be essential (Yamamoto, Masaki and Tashiro, 1996; Snapp et al ., 2003; Barbante et al ., 2008), while others refuting this claim (Marti et al ., 2010; Jancowski et al ., 2014; Ferrero et al ., 2015; Grados-Torrez et al ., 2021). Recently these opposing views were attempted to be reconciled into a single unified theory of OSER formation, which hypothesised multiple parallel pathways to induce OSER (Sandor et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As shown here, also proteins with only one or two membrane-spanning domains may transform the ER from a network of branching tubules to a variable number of stacked or folded membrane arrays -besides the known ER-shaping protein classes Reticulon, Lunapark, and Atlastin (reviewed in Kriechbaumer and Brandizzi, 2020). Other prominent examples are the isoforms of HMG-CoA reductase (HMGR) with two N-terminal transmembrane domains (Leivar et al, 2005;Ferrero et al, 2015;Grados-Torrez et al, 2021) and splice variant YUC4.2 with C-terminal tail anchor that is mainly expressed in Arabidopsis flowers (Kriechbaumer et al, 2012). Initially analyzed in plant cells (termed "membrane zippering"; Mullen et al, 2001), and later coined OSER (for "organized smooth endoplasmic reticulum") based on the studies in yeast and animal cells (Snapp et al, 2003), the formation of ER subdomains is a dynamic event, mainly governed by the principles of self-organization (Borgese et al, 2006).…”
Section: Figurementioning
confidence: 95%
“…When only the N-terminal G6PD5.4 domain was used, there was still a tendency for the reporter fusions to accumulate in focal ER sites. Hence, similar to HMGR with two N-terminal transmembrane regions and multimerization among the catalytic domains (Friesen and Rodwell, 2004;Leivar et al, 2005;Grados-Torrez et al, 2021), the membrane-bound G6PD5 proteoforms tend to cluster at the ER, likely promoted by dimerization -and when this occurs between proteins in opposing membranes, OSER long-chain fatty acids (VLCFAs) as precursors of sphingolipids, triacylglycerols (TAG), cutins, and waxes. (B) In the phenylpropanoid pathway (starting from plastid-exported phenylalanine, Phe), CAD is directly NADPH-dependent, whereas C H, C H, and F H are cytochrome P enzymes (white asterisks) that depend on NADPH:cytochrome P oxidoreductase (ATR) for reduction in the synthesis of lignin and flavonoids.…”
Section: Figurementioning
confidence: 99%
“…It has been demonstrated that toxisome structure is an organized smooth ER (OSER) [24], which is a drastic remodeling in ER morphology resulting from smooth ER proliferations [39]. Previous studies have reported various OSER structures in yeast [40][41][42], mammalian [39,[43][44][45], and plant cells [46,47], that can be induced by overexpression of some resident ER transmembrane proteins including HMG-CoA reductase (HMGR) [42,46,48], Sec61 [39], and cytochromes P450 or b5 [39,41,49]. In Arabidopsis thaliana and Nicotiana benthamiana, the OSER structure induced by HMGR-GFP overexpression appeared with hypertrophied aggregates near the nucleus as observed by confocal microscopy [46], which is different from OSER structures induced by HMGR in yeast [42] and in Fusarium.…”
Section: Plos Pathogensmentioning
confidence: 99%